The weight of ink eaudiobook - Kadish, Rachel (HighBridge Audio, 2017)
Set in London of the 1660s and of the early twenty-first century, The Weight of Ink is the interwoven tale of two women of remarkable intellect: Ester Velasquez, an emigrant from Amsterdam who is permitted to scribe for a blind rabbi, just before the plague hits the city; and Helen Watt, an ailing historian with a love of Jewish history. As the novel opens, Helen has been summoned by a former student to view a cache of seventeenth-century Jewish documents newly discovered in his home during a renovation. Enlisting the help of Aaron Levy, an American graduate student as impatient as he is charming, and in a race with another fast-moving team of historians, Helen embarks on one last project: to determine the identity of the documents' scribe, the elusive "Aleph." Electrifying and ambitious, sweeping in scope and intimate in tone, The Weight of Ink is a sophisticated work of historical fiction about women separated by centuries, and the choices and sacrifices they must make in order reconcile the life of the heart and mind.